Distribution and Pools of Soil Organic Carbon in Chernozemic Soils Impacted by Intensive Farming and Erosion in the Loess Plateau in South-East Poland - Beata Labaz; Joanna Beata Kowalska; Cezary Kabala; Mirosław Kobierski; Jaroslaw Waroszewski; Michal Dudek; Katarzyna Szopka; Dariusz Gruszka (Agronomy)
Soil erosion and the loss of soil organic carbon (SOC) pools are considered serious environmental problems in undulating landscapes on loess covers, accompanied in some areas, such as south Poland, by the physical degradation of chernozemic soils. The aim of the present study was to identify the scale and reasons for spatial variation of the SOC pools in the intensely cultivated Luvic Phaeozems in one of the unique patches of chernozemic soils in Poland. This study, carried out in a soil catena located in the undulating Carpathian Foreland in south-east Poland, has demonstrated that the SOC pools can greatly differ on a very small scale, even in relatively less differentiated landscapes and in soils classified into the same group. The scale and reasons for the differentiation of the SOC pools depend on the method (depth) of calculation. The spatial differences were smaller and were mainly related to the SOC concentrations and the bulk density of the topsoil horizons, when calculated for depths of 0–30 cm and 0–50 cm. On the other hand, the SOC pools calculated for the 0–100 cm soil layer differed most significantly between the profiles in the catena, representing a continuous growing trend from the uppermost towards the lowermost part of the catena, and were clearly related to the total thickness of the humus horizon(s). The latter findings confirm that sheet erosion has a major impact on the spatial variation of SOC pools in an agricultural landscape. However, soil morphology and the distribution of SOC across the soil profiles suggest additional influences from historical pedogenesis and modern farming technology. The presence of black, thick and humus-rich chernic horizons in all soils across the catena indicates that modern farming must not degrade the soils, but, on the contrary, it can help in the restoration of even neo-formation of chernozemic soils (Phaeozems), if oriented towards the conservation of humus content, soil structure, and biological activity.